The Meaning of Leisure : Definitions and Practices among Migrant and Non-Migrant Women in an Urban Space - Sandoval, Vania L. (Leisure Studies in a Global Era, 2017)
This book deals with the concept of leisure and the everyday leisure practices of a group of diverse single women in an urban setting-Mannheim, Germany. Vania Sandoval focuses on how social structure and individual choices relate to each other in the local context. Initially, the book considers the women as a relatively homogenous group, analyzing how they conceive, organize and experience their leisure in a similar manner with individual nuances. It then proceeds to highlight some of the processes that lead, in this particular case, to migration-based differences in their leisure practices. .